2022
DOI: 10.1111/mmi.15004
|View full text |Cite
|
Sign up to set email alerts
|

Sequential action of antibacterial effectors in Dictyostelium discoideum phagosomes

Abstract: Mammalian professional phagocytic cells ingest and kill invading microorganisms and prevent the development of bacterial infections. Our understanding of the sequence of events that results in bacterial killing and permeabilization in phagosomes is still largely incomplete. In this study, we used the Dictyostelium discoideum amoeba as a model phagocyte to study the fate of the bacteria Klebsiella pneumoniae inside phagosomes. Our analysis distinguishes three consecutive phases: bacteria first lose their abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…We next analyzed the bacteriolytic activity present in extracts from kil1 KO cells. Kil1 is the main sulfotransferase in D. discoideum cells, and kil1 KO cells show a decreased ability to kill and destroy K. pneumoniae bacteria [5,9], and to a lesser extent, E. coli bacteria [4]. As previously reported [6], extracts from kil1 KO cells exhibited a strongly reduced ability to lyse K. pneumoniae bacteria (Fig.…”
Section: Bacteriolytic Activity In Extracts From D Discoideum Mutant ...supporting
confidence: 76%
See 1 more Smart Citation
“…We next analyzed the bacteriolytic activity present in extracts from kil1 KO cells. Kil1 is the main sulfotransferase in D. discoideum cells, and kil1 KO cells show a decreased ability to kill and destroy K. pneumoniae bacteria [5,9], and to a lesser extent, E. coli bacteria [4]. As previously reported [6], extracts from kil1 KO cells exhibited a strongly reduced ability to lyse K. pneumoniae bacteria (Fig.…”
Section: Bacteriolytic Activity In Extracts From D Discoideum Mutant ...supporting
confidence: 76%
“…We analyzed previously the phenotypes of a collection of D. discoideum mutants and showed that different D. discoideum gene products are required to destroy different bacterial species in living cells [4]. Our results also demonstrated that bacterial death in phagosomes precedes the permeabilization of its membrane(s) and its gradual dismantling by digestive enzymes [5].…”
Section: Introductionmentioning
confidence: 77%
“…We then replaced the buffer with LB medium containing a small amount of paraformaldehyde and increased the temperature to 37°C (Figure 5a). These conditions kill D. discoideum cells, but allow bacterial growth (Crespo‐Yanez et al., 2022). As a control, we also measured growth of bacteria incubated in the absence of D. discoideum cells (Figure 5a,d).…”
Section: Resultsmentioning
confidence: 99%
“…Viable bacteria were defined here as bacteria which can grow in LB and this was measured as described previously (Crespo‐Yanez et al., 2022). Briefly, cells were mixed with bacteria as described above, and observed for 25 min instead of 2 h (movie 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation